(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the quality of life status using the EQ-5D-5L instrument among patients with heart failure who are hospitalized at the Cardiology Department of Huu Nghi Hospital, Hanoi, in 2024. Methods: A cross-sectional study was conducted on 75 inpatients at the Cardiology Department of Huu Nghi Hospital from March 2023 to May 2024. Results: The mean quality of life index among hospitalized heart failure patients, measured by the EQ-5D-5L scale covering five dimensions (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression), was 12.89 ± 3.508. Specifically, 45.6% of patients had a moderate level of quality of life, followed by 24.1% with a high level and 27.8% with a low level. A very high quality of life was observed in 2.5% of patients, while none were classified as having a very low quality of life. Conclusion: The quality of life among hospitalized patients with heart failure was at a moderate level according to the EQ-5D-5L scale.